Emergency endodontic care for permanent teeth in children: Patterns, treatment outcomes, and challenges in Trinidad, West Indies - Tricia Percival; Kelee Bascombe (Arbu Academic Publishing, 2024)
Aim: The aim of this study was to assess the patterns and treatment outcomes of permanent teeth requiring emergency endodontic care in children and to highlight the challenges encountered in obtaining this care at the Child Dental Health Unit, School of Dentistry, University of the West Indies, St. Augustine, Trinidad. Methods: This study was conducted through a retrospective analysis of pediatric patients requiring emergency endodontic treatment of permanent teeth at the Child Dental Health Unit clinic from January 2016 to December 2019. Data were collected via file record reviews and telephone interviews with the patients' parents or caregivers, using standardized questions. The collected data included the patient's age, sex, tooth involved, reasons for endodontic treatment, type of treatment provided, stage of endodontic treatment attained, and completion time. The data were then formatted and analyzed using descriptive statistical methods. Results: A total of 6887 patients attended the Child Dental Health Unit for emergency care, of which 5% required endodontic treatment in permanent teeth. Among these, 60.5% of cases were female and 39.5% were male, with a mean age of 12.1 years. The majority of cases (77.3%) were due to caries, while 22.7% were due to trauma. Molar teeth were the most commonly treated, but only 42.9% of all emergency endodontic treatments on permanent teeth were completed. The primary reason for the non-completion of endodontic treatment was lengthy patient wait times for follow-up appointments. Conclusions: The majority of emergency endodontic cases were not completed, primarily due to delays or lack of recall by dental students and vocational trainees. Lengthy waiting times resulted in an increased need for tooth extractions. Existing services require evaluation to ensure prompt treatment, preventing delayed care, recurrent pain, infection, and tooth loss.